(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The turbidimetric and Z-potentiometric methods were used for the assessment of some properties of diatomite – bentonite based conditioners for dewatering of effluents from the digestate of a biogas plant. These physical conditioners were prepared based on natural porous highly dispersible systems such as bentonite and diatomaceous earth. Three types of modified systems in the forms of CaO were used, which differ from each other in the ratio of the content of bentonite and diatomite. The role of the silica-containing component is to ensure the structuring of these systems. Diatomite was used for this purpose.